MEMOAR BURUH MIGRAN PEREMPUAN DAN MEDIA PERLAWANAN - harjito, harjito (PALASTREN: Jurnal Studi Gender, 2018)
Catatan perjalanan hidup seseorang yang terdapatdalam memoar memuat cara pandang seseorangatas peristiwa yang diceritakannnya. Memoarburuh migran perempuan mengungkapkan carapemaknaan atas persoalan mereka. Tulisan inibertujuan mengungkap struktur memoar danpenggunaannya sebagai media perlawananburuh migran perempuan. Dalam menganalisismemoar, dipergunakan pendekatan sosiologisastra. Bangunan strukur memoar terdiri dariempat pola tentang simbol sukses, naiknya statussosial, cara menghadapi dan cara memaknaipenderitaan. Bangunan inimencerminkan upayamereka dalam menghadapi penderitaan dankesuksesan sebagai situasi sosial pengarangnya.Memoar membuka penafsiran yang berbeda atasmakna hidup sukses bagi buruh migran. Memoarjuga merupakan alternatif perlawanan bagiburuh migran perempuan dalam menghadapiproblem sosial yang dihadapi yaitu menegasikisah hidup sukses buruh migran yang tumbuhdan berkembang dalam budaya lisan.Kata kunci: Buruh migran , narasi memoar,pengalaman perempuanThe journey note of life of a person in the memoirscontains a person’s perspective on the events she/he told.The memoirs ofwomen migrant workers reveals waysto interpret their problems. This paper aims to revealthe structure of memoirs and their use as a resistancemedia for women migrant workers. In analyzingthe memoirs, the sociology of literature is used. Thememoirs building structure consists of four patternsi.e. the symbol of success, the rising of social status,how to deal with and how to interpret suffering. Thisbuilding reflects their efforts in dealing with sufferingand success as the author’s social situation. Memoirsopen up different interpretations of the meaning ofsuccessful life for migrant workers. Memoir sare alsoan alternative to resistance for women migrant workersin dealing with social problems faced. Memoirs arean alternative to the resistance of women migrantworkers. Memoirs are a living part of women migrantworkers who seek to fight against the success storiesof women migrant workers growing and developing inoral cultures.Keywords: migrant workers, narrative memoirs,women’s experiences